Highly efficient two-dimensional beam steering using all-dielectric fiber metatip. (April 2022) - Sinha, Rajat K.; Sharma, Shubhanshi; Bag, Saawan; Kar, Sauradeep; Lahiri, Basudev; Varshney, Shailendra K.
Highlights: Two-dimensional beam steering using single-mode fiber all-dielectric meta -tip. Optical fiber based Metalens shows superior performances (focal length and FWHM). High diffraction and transmission efficiency of 61.3% and 70.5% and focusing efficiency of >82%. The proposed fiber all-dielectric metatip will be useful in optical beam forming network, fiber to fiber coupling, fiber to free space coupling, biosensing, and endoscopy. Abstract: Optical dielectric metasurfaces have produced a breakthrough in the field of high transmission wavefront engineering. However, its integration with the optical fiber platform is relatively new and has huge potential applications in imaging, sensing, and communication. In this work, we discuss the design and simulation of an all-dielectric metasurface that has been mounted on a conventional single-mode fiber (SMF-28) facet. It has been shown that it is possible to steer the optical beam in a two-dimensional space through appropriate design of the requisite metasurface, supported by both theoretical and simulation results. Numerical simulations reveal that the designed fiber-metatip can work efficiently over the standard telecom C-band with a bandwidth of 60 nm. In addition, the capability of meta -lensing with a focal length of 10 μm, FWHM of ∼1.439 μm and focusing efficiency of 82.2% has been demonstrated. The proposed Fiber meta -tip outperforms in compare to commercially available lensed fibers.